Assessing the Construct Validity and Reliability of School Health Records Using the 'Health Dialogue Questionnaire' in the Eleventh Grade - Malin Rising Holmstrom; Niclas Olofsson; Lisbeth Kristiansen (AIMS Press, 2016)
The aim for this study was to assess the construct validity and reliability of the Health Dialogue Questionnaire (HDQ©) for eleventh grade in school through comparison of the HDQ© with Paediatric Quality Of Life Inventory (PedsQLTM), Local monitoring of youth policy questionnaire (LUPP®), Health behaviour in Swedish school-aged children (HBSC©), Equal health (EH©) and The Swedish Survey Youth on Alcohol Consumption (SSYAC©). Methods: Cross-sectional samples of eleventh graders from the academic year 2009/2010 was used from the HDQ© (n = 2752), the HBSC© (n = 2090), the PedsQLTM (n = 666), the "LUPP®" questionnaires (n = 2400), EH© (n = 258), and SSYAC© (n = 1748) in the academic year 2009/2010. A comparison between HDQ© and the different proxies was done. Exploratory and confirmatory factor analyses were performed as well as a Multitrait-Multimethod Matrix (MTMM), in order to evaluate the construct validity and reliability of HDQ©. Results: An average disagreement between HDQ© and proxies with 10 percentages was found. Exploratory factor analysis of HDQ© on the 2009/2010 sample suggested a four factor solution (girls factor solution 65% of total variance explained, and in the boys' solution 59% of total variance explained). A second sample 2010/2011 of eleventh graders were used for the confirmatory solution. Almost perfectly similar four factor solutions with were found (girls 58% of total variance explained and boys 56% of the total variance explained). Using MTMM the reliability was generally high and HDQ© and showed agreeable validity. Discussion and conclusions: The HDQ© questionnaire is a reliable and valid instrument for measuring eleventh graders self-reported-health in school.